BAHASA INDONESIA LEARNING COMMUNICATION BY USING COOPERATIVE MODEL APPROACH - Syaiful Rohim (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
Communication in education and learning gives a great contribution in the success and effectivity learning achievement which is expected. The same as a teachers when they making communication in the class. There are a lot of model and innovation in learning communication, for example Cooperative Learning (CL), Contextual Teaching and Learning (CTL), Inquiry, and Problem Solving. This learning model concern that every learning process of active students create their own knowledge (student centered). By using positivisme percepective that tends to avoid talking about reality which is can not be observed (Rohim, 225:2009). The approach which is used in this research is using quantitative approach because it is needed to measure the impact of indepent variable to dependent variable, in other words to measure the cause and effect (causal), (Sugiyono, 2010:190). This research shows that learning strategy and cooperative communication significantly give a big impact to students’ achievement, this data is supported with the data that shows students’ learning achievement in Bahasa Indonesia is better than students’ learning achievement which is using convensional group learning strategy.